Veterans and violence: An exploration of pre-enlistment, military and post-service life. (November 2018) - Banks, James; Albertson, Katherine
Despite growing criminological interest in the many ex-service personnel mired within the UK's criminal justice system, there remains a paucity of qualitative research studies examining the (violent) veteran offender. In response, this paper mobilizes the voices of veterans to explore the key life events that can shape their offending behaviour. Countering reductionist explanations of violent crime committed by ex-service personnel, we contend that veterans' violence may be rooted within personal biographies and psyches, conditioned by military experiences and represent the psychosocial consequences of the socioeconomic transformations of advanced capitalism.